On the rate of convergence of the ECME algorithm - Mkhadri, Abdallah (Statistics & probability letters, 1998)
This paper deals with the matrix rate of convergence of the ECME algorithm, a simple extention of EM and ECM algorithms proposed recently by Liu and Rubin. We establish a general formula for the matrix rate of convergence of ECME which is a generalization of the result of Liu and Rubin.